Data from: RNA Sequencing Provides Novel Insights Into the Transcriptome of Aldosterone Producing Adenomas - Tobias Åkerström; Per Hellman; Peyman Björklund (Uppsala University, 2019)
RNA-Seq data from fifteen aldosterone producing adenomas. Whole Genome Sequencing data from two aldosterone producing adenomas and one normal peripheral blood sample.
Keywords: Nucleotide sequence data; Medical and Health Sciences; Medicin och hälsovetenskap